Gelatin-polyethylenimine composite as a functional binder for highly stable lithium-sulfur batteries. (20th August 2018) - Akhtar, Naseem; Shao, Hongyuan; Ai, Fei; Guan, Yuepeng; Peng, Qifan; Zhang, Hao; Wang, Weikun; Wang, Anbang; Jiang, Bingyin; Huang, Yaqin
Abstract: Lithium-sulfur (Li-S) batteries with high specific capacity are expected to be a new generation of energy storage devices. However, the shuttle effect of lithium polysulfide makes it difficult to commercialize stable Li-S batteries. In this work, we designed a gelatin-polyethylenimine composite (GPC) as functional binder for Li-S batteries to improve the stability of electrode during discharge-charge process. GPC binder combines the dispersion and adhesion ability of gelatin, which keeps cathode homogeneous and stable during electrochemical reaction, and adsorption capability of PEI for polysulfide, which suppresses the "shuttling effect". The result shows that GPC used as a binder remarkably enhanced cyclic performance of Li-S battery with good capacity retention of about 100% at current density of 1C (sulfur loading 1.5 mg cm −2 ) after 100 cycles. We believe that GPC would be a promising binder for highly stable Li-S batteries. Graphical abstract: Designed gelatin-polyethylenimine composite as a functional binder for highly stable lithium-sulfur batteries. Image 1 Highlights: GPC binder provides a strong link between sulfur and conductive agents. GPC binder keeps electrode homogeneous and stable during cycling. GPC confines the dissolved Li2 Sx and increase the sulfur utilization. GPC accommodates the volume changes during the electrochemical reaction.